Reviving the Ruins of Berenice in the Sidi Khrebish Area of Benghazi Old City by Using Holographic Technology - A. Gumma , Fathea; G. Trabelsi, Zoha (Scientific Journal of University of Benghazi, 2024)
The city of Benghazi contains rich archaeological and historical monuments that form the spirit of the city, its civilization, and its ancient history, which needs to be preserved and revived in order to preserve the cultural and historical heritage of the city and its buildings and sites. Sometimes preservation involves many different aspects, such as celebrating events, people, places, and ideas that we are proud of. It also sometimes involves recognizing moments in our history that can be painful or uncomfortable to remember. Sidi Khreibish is an archaeological area of important historical value for the Old City of Benghazi in particular and for the city of Benghazi in general. Through the lighthouse, which constitutes the main landmark, it needs to be revived and presented again. With the technical development in the use of technology in architecture, especially in virtual reality and simulation applications, it has become possible to create a virtual environment using technology to reformulate the architectural and urban heritage. This is done by illusioning the recipient’s eye with non-existent 3D models or surfaces that are shaped in a vacuum using advanced hologram techniques and presenting it as a default model. The current study included an integrated analysis of the study area and how the holographic imaging technique could be used, which has a unique feature that enables it to recreate the image of the original objects in its three dimensions to a very high degree, in order to re-embody the Old City and highlight its features of great historical value for the region and revive it within the fabric of the urban city. KEYWORDS: , , , .